Glass Half Full : Poverty Diagnostic of Water Supply, Sanitation, and Hygiene Conditions in Tajikistan - World Bank Group (World Bank, Washington, DC, 2017)
Located on the western tip of the Himalayas, Tajikistan has abundant fresh water resources in its rivers, lakes, and glaciers. Yet, access to improved drinking water, and to sanitation connected to a functioning sewerage system, are among the most severe and unequally distributed services in the country. Unsafe water supply, sanitation and hygiene (WASH) conditions have significant adverse effects on well-being, particularly for rural residents, the poor and the children. Glass Half Full: Poverty Diagnostic of Water Supply, Sanitation, and Hygiene Conditions in Tajikistan documents the realities, characteristics, and priorities of Tajikistan’s WASH-deprived population. It presents new, comprehensive evidence on the coverage and quality of WASH service conditions, along with their diverse well-being impacts. It also identifies institutional gaps and service delivery models that can inform future policies and investments in the WASH sector. The findings communicate a sense of urgency that should inspire the government, civil society, and the international community to accelerate their actions toward addressing WASH deprivation in Tajikistan.